SISTEM INFORMASI PEMASARAN PRODUK BERBASIS WEB PADA GALERI FOTO - Fenny Purwani; Rendy Febriayana; Duwi Febyanti; Tiara Meftahul Jannah (CV. Denasya Smart Publisher, 2024)
The web-based product marketing system in the photo gallery aims to increase the vision and accessibility of the products offered. The method used in developing this system is the System Development Life Cycle (SLDC), which includes planning, analysis, design, implementation and maintenance stages. This research aims to design and implement an information system that can make it easier for users to search for and obtain information related to products available in the gallery. The results of system development show significant improvements in market reach and marketing process efficiency, with users able to access product information more quickly and easily. With this system, it is hoped that the photo gallery can attract more customers and increase sales of the products offered.